Pembuatan Payasan Agung Wedding Bali Khas Gianyar Dengan Teknik Tatah Logam: Payasan Agung Khas Gianyar - Raditya Wayan; Rai Sunarini Ni Made; Ngidep Wiyasa I Nyoman (Hastagina : Jurnal Kriya Seni, 2026)
Metal carving art is a cultural heritage of traditional Indonesian visual arts that possesses high aesthetic value and uniqueness. In Bali, this art is manifested in the form of Payasan Agung for wedding ceremonies, which consists of ornaments such as badong, pending, gelang kana, gelang naga satru, and subeng cerorot. Singapadu Village, Gianyar Regency, is known as one of the centers of metal craft with rich tradition and distinctive craftsmanship techniques. The sustainability of this art faces challenges such as decreasing regeneration of young artisans, high costs of raw metal materials, and increased use of synthetic raw materials that are more practical and affordable. This research aims to examine the process of making Gianyar-style Payasan Agung, including procedural techniques, raw material selection, and the embedded cultural values. The creation process involves three main stages: exploration, design, and realization. The exploration stage involves searching for concepts and determining traditional motifs such as patra punggel, mas-masan, cracap, and batun poh. The design stage includes creating sketches according to proportion and function, while the realization stage employs traditional craft techniques such as ngecek (rancapan), meludan (wudulan), and nyawi (terawangan), followed by sanding, setting gemstones, and gold plating as the final step. The outcomes include five main types of ornaments: tajuk, petitis, badong, bros, and pending, each representing Balinese aesthetic, symbolic, and philosophical values.